Subjective well-being : efforts to improve through gratitude training on millennial employees - Pamungkas, Endah Ayu; Kamsih Astuti,; Reny Yuniasanti, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Millennial employees who have subjective well-being will positively respond to events or incidents in the surrounding environment. Subjective well-being is defined as an assessment of the subjective well-being of an individual to view past experiences. Individuals who have high subjective well-being will be able to recognize and acknowledge the goodness that occurs in every problem they experience to generate positive feelings when addressing these problems. This study aims to see whether gratitude training can improve subjective well-being in millennial employees. The subjects used in this study were millennial employees at Company X. The samples taken were 20 millennial employees who fall into the category of low to moderate subjective well-being. The research method used was a quasi-experimental method with a scale as a data collection tool. The scale used in this study was a subjective well-being scale (SWLS and SPANE) and used a gratitude training intervention. Data analysis used was independent sample t-test and paired sample t-test. The independent sample t-test analysis showed that the Mean post-test of the experimental group was 76.60, and the Mean post-test of the control group was 23.30 with a t-value 19.625 (p<0.01). It means that there were differences in subjective well-being in the experimental group and the control group. While the paired sample t-test analysis showed the results of the Mean pretest value of the experimental group was 51.10 and the Mean post-test value of the experimental group was 76.60 with a t-value -10.218 (p<0.01), which means that there were differences in subjective well-being in the pretest and post-test of the experimental group. This finding can provide evidence that gratitude training can increase subjective well-being in millennial employees.